The education of the future: beyond the classroom - Timmer, Ainhoa Katharina; Mosquera Gende, Ingrid; Conde del Río, Alba (12th International Technology, Education and Development Conference (INTED), 2021)
This project aims to analyse different studies with the objective of outlining potential scenarios concerning the education of the future. To travel forward to tomorrow's world is still a pending subject for mankind. However, there is the possibility of debating and predicting some aspects based on the daily life and surroundings in which human relationships develop. As a result, we will firstly aim to place the reader at a specific moment and in a particular space in order to subsequently begin to analyse possible educational contexts in more detail. This includes not only physical but also virtual educational spaces. It is therefore implicit that we should mention the resources needed in order to face the challenges of the future, making specific references to new technologies. With regards to the latter, it will be necessary to take into account the methodologies and changes which these might undergo in order to adapt to the needs of educators and students who will mark out the new ways of teaching and learning. In the same way, it is essential to address the role which educators should adopt when faced with new situations as well as how they should retrain to confront the education of the future. This is an adaptation that they should carry out in conjunction with parents and pupils. Through all this, the aim is to offer a global and introductory vision of possible educational scenarios of the future. We will take into consideration the fact that society and technologies are forever advancing and that, due precisely to this uncertainty, we should train teachers and prepare our students.
Keywords: education; future; classroom; educational context; virtual educational spaces; methodology; role; new technologies; WOS(2)